5 Comparison of treatment outcomes in very elderly patients (>85years) with severe symptomatic aortic stenosis. (17th July 2020) - Obaid, Daniel; Roche, Lydia; Yousaf, Adnan; Hill, Amanda; Hailan, Ahmed; Bhatti, Farah; Ashraf, Saeed; Zaidi, Afzal; Kumar, Pankaj; Youhana, Aprim; Aldalati, Omar; Smith, Dave; et al.
Abstract : Introduction: Due to the demographics of our patient population our institution has a high incidence of very elderly (>85 years) patients with severe symptomatic aortic stenosis. We examined the outcomes of these patients following trans-catheter aortic valve implantation (TAVI), surgical aortic valve replacement (SAVR) or medical therapy. Methods: We included all patients >85 years of age with symptomatic severe aortic stenosis referred to our tertiary centre for consideration of aortic valve intervention between 2009 and 2016. Following assessment by the TAVI team (2 cardiologists and 2 cardiac surgeons) patients underwent SAVR or TAVI. Patients deemed unsuitable or refusing intervention had medical therapy. Data was obtained from electronic databases and clinical case notes. Results: 309 patients were included (86 TAVI, 133 SAVR and 90 medical). Comparing patients undergoing TAVI and SAVR, TAVI patients were older (mean age 89.4 years vs. 86.9, p<0.01) and more likely to have had previous cardiac surgery (21% vs. 2%, p<0.01). SAVR patients were more likely to have coronary disease (62% vs. 48% p=0.04). There was no statistical difference in the other characteristics (table 1 ). Compared with patients undergoing intervention the medically treated had higher mean creatinine values (132μmol/L, p<0.01) and compared to the SAVR patients were older (89.0 years, p<0.01) with more previous cardiac surgery (13%, p<0.01). They also had less documented coronary disease (33%, p<0.01) (but did not undergo routine angiography). All TAVI patients had surgical access (86% trans-femoral, 8% trans-apical, 6% direct aortic), an Edwards (XT or Sapien 3) valve and general anaesthetic in 69% of cases. There were no intraoperative deaths but 3 conversions to sternotomy for bleeding. 68% of the surgical patients underwent isolated AVR and 32% AVR+CABG with 1 surgical intraoperative death. Medically managed patients had poor outcomes with a mortality of 49% at 1 year and 77% at 3 years. Survival of patients with either intervention was better, with no significant difference in 30-day mortality of SAVR and TAVI (5.3% vs 2.3%, p=049) or 3-year mortality (33% vs. 36%, p=0.66) respectively (figure 1 ). Compared with TAVI, SAVR patients spent significantly more days on ITU/HDU (8.31±12 vs. 0.96 ±1.7, p<0.01) and in hospital (21.69±24 vs. 11.89 ±9.9, p<0.01). SAVR patients had more pulmonary complications than TAVI (26% vs. 11%, p=0.02.) 17% of the SAVR and all the TAVI pulmonary complications were chest infections but SAVR patients also required 19 chest drains insertions and 6 reintubations. There were no significant differences in the other outcomes (table 2 ). Finally, whilst acute kidney injury (AKI) rates were statistically similar, all but 1% of the TAVR patients resolved spontaneously where as 13% of the SAVR patients required renal replacement therapy p<0.01. Conclusion: The prognosis of patients >85 years of age with symptomatic severe aortic stenosis without intervention is poor. Aortic valve intervention in very elderly patients has acceptable mortality out to 3 years. In our early experience, using surgical access and high rates of general anaesthesia, TAVI in this group had similar mortality to SAVR but with significant reductions in both ITU and overall hospital stay. Conflict of Interest: none